Skin Penetration And Lag Times Of Neat And Aqueous Diethyl Phthalate, 1,2-Dichloroethane And Naphthalene - Frederick Frasch, H.; Barbero, Ana M.; Alachkar, Houda; McDougal, James N. (Cutaneous and ocular toxicology, 2007)
Cutaneous exposures to occupational chemicals may cause toxic effects. For any chemical, the potential for systemic toxicity from dermal exposure depends on its ability to penetrate the skin. Most laboratory studies measure chemical penetration from an aqueous solution through isolated human or laboratory animal skin, although most exposures are not from pure aqueous solutions. The US EPA Interagency Testing Committee (ITC) mandated by the Toxic Substances Control Act, has required industry to measure the in vitro penetration of 34 chemicals in their pure or neat form (if liquid). The goal of the present study was to measure skin permeability and lag time for three neat chemicals of industrial importance, representing the general types of chemicals to be studied by the ITC (non-volatile liquids, volatile liquids, and solids), and to examine interlaboratory variation from these studies. Steady state fluxes and lag times of diethyl phthalate (DEP, slightly volatile), 1,2-dichloroethane (DCE, highly volatile), and naphthalene (NAP, solid) were studied in two different laboratories using different analytical methods. One lab also measured fluxes and lag times from saturated aqueous vehicle. Static diffusion cells, dermatomed hairless guinea pig skin, and gas chromatography were used to measure skin penetration. In the two laboratories, the steady state fluxes (mean±SD; µg cm−2hour−1) of DEP applied neat were: 11.8±4.1 and 23.9±7.0; fluxes of DCE (neat) were 6280±1380 and 3842±712; fluxes of NAP from powder were 30.4±2.0 and 7.5±4.7. Compared with neat fluxes measured in the same laboratory, flux from saturated aqueous solution was higher with DEP (1.9 ×) but lower with DCE (0.17 ×) and NAP (0.45 ×). The three chemicals studied including a dry powder, demonstrate the potential for significant dermal penetration.